EFFECTIVENESS OF LONG PULSED ND YAG LASER IN HAIR REMOVAL - Noor, Sahibzada Mahmood; Paracha, Muhammad Majid (Journal of Postgraduate Medical Institute, 2011)
Objective: Material and Methods: 2 Results: completed the study. The maximum hair reduction was observed after first treatment 73%, after 3 months the hair reduction was 70%, whereas the response to treatment was 65% at the end of six months after the treatment. Maximum hair reduction was observed after the first treatment in all the patients. All the patients Conclusion: Long pulsed Nd YAG laser is a safe and effective method for hair reduction in all skin types involving the face. of 30 to 50 J/cm ). Four consecutive laser treatments were delivered to all the patients at 4- to 6-week intervals. Photographic evaluations and hair count of skin sites were obtained at baseline, immediately, and at 1, 3, and 6 months after the final laser treatment. Fifty adult patients (skin phototypes II–V) with dark terminal facial hair and normal hormonal profile were treated with a long-pulsed Nd:YAG laser (1064 nm, 10-mm spot size, fluence To evaluate the effictiveness and safety of long pulsed Nd:YAG laser in hirsutism.